Election process as a factor of youth socialization - Matveeva E. A. (Interactive science, 2018)
the analysis of the process of political socialization of youth and its factors is given in the article. The article covers urgent issues of political organizations influence on the process of adoption of values, standards and attitudes by an individual. It was formed in youth attitudes and behavior patterns that determine the strategy for the development of national and humanistic traditions, political culture and tolerance. And the role of political socialization of the younger generation in this connection it is important.
Keywords: социализация; молодежь; идентификация; избирательный процесс; политическая культура; youth; socialization; identification; политическая социализация; political socialization; electoral process; political culture